Screening and management of gestational diabetes in Mexico: results from a survey of multilocation, multi-health care institution practitioners - Dainelli L (Dove Medical Press, 2018)
Livia Dainelli,1 Alberto Prieto-Patron,1 Irma Silva-Zolezzi,1 Sandra G Sosa-Rubi,2 Salvador Espino y Sosa,3 Enrique Reyes-Muñoz,4 Ruy Lopez-Ridaura,5 Patrick Detzel1 1Nestlé Research Center, Lausanne, Switzerland; 2Health Economics Department, National Institute of Public Health, Cuernavaca, Morelos, Mexico; 3Clinical Research Branch, National Institute of Perinatology Isidro Espinosa de los Reyes, Mexico City, CDMX, Mexico; 4Endocrinology Department, National Institute of Perinatology Isidro Espinosa de los Reyes, Mexico City, CDMX, Mexico; 5Center for Research on Population Health, National Institute of Public Health, Cuernavaca, Morelos, Mexico Purpose: To identify the most common practices implemented for the screening and treatment of gestational diabetes mellitus (GDM) and to estimate the GDM clinician-reported proportion as a proxy of the incidence in Mexico. Materials and methods: Three hundred fifty-seven physicians in four major cities were asked about their practices regarding GDM screening, treatment, clinical exams, and health care staff involved in case of GDM diagnosis, as well as the percentage of women with GDM they care for. Data management and statistical analyses were done with Stata 13. Results: The overall GDM clinician-reported proportion was 23.7%. Regional differences were expected and consistent with the data on the epidemiology of the obesity in the country. The most common screening test was the oral glucose tolerance test 75 g one step (46.6% of total cases). Diet and exercise were sufficient to treat GDM in 40.6% of cases; the rest of the sample relied on some form of medication, especially oral hypoglycemic agents (63.0% of cases), insulin (22.0%), or a combination of these (13.0%). To educate women on how to measure glycemia and eventually take medications, an average of 2–3 hours were necessary. The three most common prenatal screening tests were the “no stress”, the “Doppler ultrasound”, and the “biophysical profile”, respectively, taken at least once by 70%, 60%, and 45% of women. Among women who were prescribed insulin, only 37% managed to keep the initial prescribed dose during the whole pregnancy. Conclusion: The survey confirmed the expected incidence and gave interesting results on the treatment of GDM. The current Mexican guidelines seem to have been partially implemented in practice, and a coherent national strategy for GDM is still missing. More studies are encouraged to investigate this topic, with the aim to better understand the importance of the monetary cost of GDM, which is currently underestimated. Keywords: GDM incidence, pharmacological treatment, prenatal test